Diagnostic and prognostic role of circRNAs in pancreatic cancer: a meta-analysis - Zhao, Ruihua; Han, Zhuo; Zhou, Haiting; Xue, Yaru; Chen, Xiaobing; Cao, Xinguang (Frontiers in Oncology, 2023)
Background: Circular RNAs (circRNAs) are types of endogenous noncoding RNAs produced by selective splicing that expressed highly specifically in various organisms and tissues and have numerous clinical implications in the regulation of cancer development and progression. Since circRNA is resistant to digestion by ribonucleases and has a long half-life, there is increasing evidence that circRNA can be used as an ideal candidate biomarker for early diagnosis and prognosis of tumors. In this study, we aimed to reveal the diagnostic and prognostic value of circRNA in human pancreatic cancer (PC). Methods: A systematical search for publications from inception to 22 July 2022 was conducted on EMBASE, PubMed, Web of Science (WOS) and the Cochrane Library databases. Available studies that circRNA expression in tissue or serum association with the clinicopathological, diagnostic and prognostic values of PC patients were enrolled. The odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were used to evaluate clinical pathological characteristic. Area under curve (AUC), sensitivity and specificity were adopted to assess diagnostic value. Hazard ratios (HRs) was utilized to assess disease free survival (DFS) and overall survival (OS). Results: This meta-analysis enrolled 32 eligible studies including 6 on diagnosis and 21 on prognosis that accounted for 2396 cases from 245 references. For clinical parameters, high expression of carcinogenic circRNA were significantly associated with degree of differentiation (OR=1.85, 95%CI=1.47-2.34), TNM stage (OR=0.46, 95%CI=0.35-0.62), lymph node metastasis (OR=0.39, 95%CI=0.32-0.48), and distant metastasis (OR=0.26, 95%CI=0.13-0.51). As for clinical diagnostic utility, circRNA could discriminate patients with pancreatic cancer from the controls, with AUC of 0.86 (95% CI: 0.82-0.88), a relatively high sensitivity of 84% and specificity of 80% in tissue. In terms of prognostic significances, carcinogenic circRNA was correlated with a poor OS (HR=2.00, 95%CI: 1.76-2.26) and DFS (HR=1.96, 95%CI: 1.47- 2.62). Conclusion: In summary, this study demonstrated that circRNA may act as a significant diagnostic and prognostic value biomarker for pancreatic cancer.